The Protective Effects of Alpha-Lipoic Acid and Coenzyme Q10 Combination on Ovarian Ischemia-Reperfusion Injury: An Experimental Study. (15th August 2016) - Tuncer, Ahmet Ali; Bozkurt, Mehmet Fatih; Koken, Tulay; Dogan, Nurhan; Pektaş, Mine Kanat; Baskin Embleton, Didem
Abstract : Objective . This study aims to evaluate whether alpha-lipoic acid and/or coenzyme Q10 can protect the prepubertal ovarian tissue from ischemia-reperfusion injury in an experimental rat model of ovarian torsion. Materials and Methods . Forty-two female preadolescent Wistar-Albino rats were divided into 6 equal groups randomly. The sham group had laparotomy without torsion; the other groups had torsion/detorsion procedure. After undergoing torsion, group 2 received saline, group 3 received olive oil, group 4 received alpha-lipoic acid, group 5 received coenzyme Q10, and group 6 received both alpha-lipoic acid and coenzyme Q10 orally. The oxidant-antioxidant statuses of these groups were compared using biochemical measurement of oxidized/reduced glutathione, glutathione peroxidase and malondialdehyde, pathological evaluation of damage and apoptosis within the ovarian tissue, and immunohistochemical assessment of nitric oxide synthase. Results . The left ovaries of the alpha-lipoic acid + coenzyme Q10 group had significantly lower apoptosis scores and significantly higher nitric oxide synthase content than the left ovaries of the control groups. The alpha-lipoic acid + coenzyme Q10 group had significantly higher glutathione peroxidase levels and serum malondialdehyde concentrations than the sham group. Conclusions . The combination of alpha-lipoic acid and coenzyme Q10 has beneficial effects on oxidative stress induced by ischemia-reperfusion injury related to ovarian torsion.